Pellet gun trauma: An unusual and unexpected type of bone lesion. (May 2022) - Tambuzzi, Stefano; Mazzarelli, Debora; Gibelli, Daniele; Panigada, Gilberto; Merelli, Vera; Cattaneo, Cristina
Abstract: Non-powder guns in general, and especially pellet guns are acknowledged to cause important injuries, also on bone tissue. However, pellet gun-related injuries have been poorly analyzed in forensic literature and scientists may have no idea of what signs a pellet gun can leave on bone. Moreover, since such lesions are not commonly encountered in everyday forensic practice, they could be misdiagnosed. For this reason, the present study was performed to investigate and illustrate the qualitative effects of pellet guns on human bone. An experiment was performed by shooting single pellets on four adult human feet belonging to the anatomical collection of the University of Milan and CAL (Collezione Antropologica Labanof), that is the anthropological collection of the forensic anthropology lab (Labanof). An Umarex – "Beretta type 92 S″ CO2 gun was used, loaded with pellets of 4.5 mm caliber of different designs: wadcutter, round-nosed, and sharp-pointed. The shots were fired from a constant distance of 20–30 cm and with different directions and angles. X-ray analysis was carried out and three feet were later skeletonized and observed with an episcopic microscope. Macroscopically, a high penetrative capacity of all the used pellets was observed: with the only exception of the wadcutter ones, all the other types were associated with bone lesions, such as abrasions of the cortical bone, chipping and/or fractures, which in some cases were even comminuted. Microscopically, metallic traces, bone spicules, and striae-like irregularities on the bottom of all the bone abrasions were found. Finally, we provide forensic pathologists and anthropologists with some considerations and illustrations that may help in the correct diagnosis in case of need. Highlights: Pellet guns skin and bone injuries are rare and may be misdiagnosed. Abrasion, chipping, and fracture are the most typical pellet gun induced lesions. Bone spicules may help in detecting the gunshot direction. Bone abrasions due to pellet guns have a peculiar aspect.